La Tomba di Giulio II: La gloria negata - Forcellino, Maria (Incontri. Rivista europea di studi italiani, 2014)
The Tomb of Julius II. Glory Denied This article analyzes the history of Michelangelo Buonarroti’s Tomb of Julius II from the unusual point of view of the artist, rather than from the perspective of the difficulties entailed in its creation, making use of the topic’s abundant documentary tradition. Commissioned by Pope della Rovere in 1505 with the aim of creating a mausoleum in the style of antiquity, work was interrupted at the behest of della Rovere himself shortly after it began. Upon the death of the pope, work was recommenced by his heirs in 1513 and continued until 1545. After this, the popes of the sixteenth century either did their best to slow down the work or went as far as to hinder its execution, with the notable exception of Adrian VI. Both the two Medici popes − Leo X and Clement VII − and Paul III Farnese, wishing to link their names with that of Michelangelo, commissioned him to undertake great tasks: the Medici Tombs, the Last Judgement and the Cappella Paolina. These popes viewed the realization of their own commissions as more important than work on the monument to Julius II; in fact, they prevented Michelangelo from fulfilling his contractual commitments with the della Rovere by issuing special papal briefs, albeit in agreement with Michelangelo. The fate of the monument of Julius II unequivocally testifies to Michelangelo’s standing and exceptional achievement: the artist was already revered as a great master by his contemporaries and attracted patrons who swarmed around him, wishing their own glory to be celebrated only by his art. This was not only true for the Medici and Farnese popes but also for the della Rovere, who would not abandon their mission of having the monument executed by Michelangelo, to the point where they would rather wait decades for him than see it completed by any other artist. This story of the monument, which is itself the protagonist, reflects the Renaissance as a whole − in the broadest sense of the political, social and cultural development of the entire era − with all the contrast of its lights and shadows.